Cartographic analysis of the types of population densities for Diyala Governorate - Khalifah, Rana Samir; Al-Tai, Ayad Ashour Hamza (Al-Adab Journal, 2021)
This research clarified the types of population densities and their distribution at the level of administrative units for Diyala Governorate for the two years (1997-2019). Among the most prominent results of the research is the spatial variation of population density (general, rural, productive, agricultural) in the study area. There are several reasons, including the small area of the area compared to the number of its inhabitants, as well as the attractions that it was characterized by, and that among the reasons for the low population density of some areas is due to the large area of the area compared to the number of its inhabitants.